Isolation and Identification of protease producing Aeromonas hydrophila - Abd-alla, Maeis T; Jasim, Hameed M; Hussein, Asmaa A (Al-Nahrain Journal of Science, 2018)
A total of 89 samples were collected from pools of fish farms and gills pieces of fresh fishes from different locations in Baghdad governorate. From these samples, a total of 91 bacterial isolates were obtained and identified as suspected Aeromonas spp. according to the cultural and microscopical characteristics. After subjection to the biochemical tests, seven isolates were identified as Aeromonas hydrophila. Results of identification were confirmed by using Api 20E system. Ability of these isolates for protease production was screened. Results showed that all the seven isolates were protease producers; among them the A. hydrophila A4 obtained from gills pieces of fresh fishes was the most efficient in protease production. Enzyme specific activity of protease of the crude filtrate of this isolate was 31.01U/mg protein.